2021
DOI: 10.1016/j.cell.2021.03.051
|View full text |Cite
|
Sign up to set email alerts
|

TOP1 inhibition therapy protects against SARS-CoV-2-induced lethal inflammation

Abstract: The ongoing pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is currently affecting millions of lives worldwide. Large retrospective studies indicate that an elevated level of inflammatory cytokines and pro-inflammatory factors are associated with both increased disease severity and mortality. Here, using multidimensional epigenetic, transcriptional, in vitro and in vivo analyses, we report that Topoisomerase 1 (TOP1) inhibition suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 81 publications
4
70
0
Order By: Relevance
“…A recent study showed that the drug plitidepsin (Aplidin), which targets the host protein eEF1A, exhibits potent anti-SARS-CoV-2 activity in cell cultures and mouse models 25 . Another US FDA-approved inhibitor topotecan (TPT) targeting topoisomerase 1 has been reported to suppress the lethal inflammation induced by SARS-CoV-2 and reduce morbidity and mortality in a preclinical mouse model 26 . Thus, identification of additional host biological pathways and corresponding drugs is urgently needed to facilitate new drug development for the treatment of the COVID-19 disease and prevent viral spread.…”
Section: Mainmentioning
confidence: 99%
“…A recent study showed that the drug plitidepsin (Aplidin), which targets the host protein eEF1A, exhibits potent anti-SARS-CoV-2 activity in cell cultures and mouse models 25 . Another US FDA-approved inhibitor topotecan (TPT) targeting topoisomerase 1 has been reported to suppress the lethal inflammation induced by SARS-CoV-2 and reduce morbidity and mortality in a preclinical mouse model 26 . Thus, identification of additional host biological pathways and corresponding drugs is urgently needed to facilitate new drug development for the treatment of the COVID-19 disease and prevent viral spread.…”
Section: Mainmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 26, 2021. ; https://doi.org/10.1101/2021.05. 26.445787 doi: bioRxiv preprint (IL)-6 and IL-8 (5,7,8). In certain cases, massive inflammatory responses occur due to hyper-activation of the immune system, resulting in a widespread and uncontrolled cytokine storm, leading to acute respiratory distress syndrome (ARDS), life-threatening lung damage, and increased mortality of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with remdesivir, clofazimine exhibited antiviral synergy in cell culture and animal models [ 2 ]. Topotecan suppresses infection-induced inflammation, thus reducing morbidity and rescuing mortality in a transgenic animal model [ 3 ]. However, the efficacies of these drugs on patients await further clinical investigation.…”
Section: Introductionmentioning
confidence: 99%